2005
DOI: 10.1007/s00240-005-0473-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of electro-acupuncture compared to sedo-analgesics in relieving pain during shockwave lithotripsy

Abstract: The aim of this study was to compare the clinical efficacy of electro-acupuncture (EA) with the combination of tramadol+midazolam (TM) for pain relief during outpatient extracorporeal shockwave lithotripsy (ESWL). A total of 35 patients (20 men, 15 women) with stones located in the pelvicalyceal system of the kidney were randomized prospectively to undergo lithotripsy with a third generation lithotriptor (Stone Lith, smart PCK) after receiving either EA (n=17) or TM (n=18) for sedation and analgesia. EA treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…It has been proposed as an alternative and effective analgesic with few side effects (29), rapid recovery to work (30) and rare complications (31)(32)(33)(34).…”
Section: Historical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed as an alternative and effective analgesic with few side effects (29), rapid recovery to work (30) and rare complications (31)(32)(33)(34).…”
Section: Historical Considerationsmentioning
confidence: 99%
“…In the literature, acupuncture has been described to aid in the management of chronic prostatitis, chronic pelvic pain as well as nocturnal enuresis (29,(36)(37)(38). In stone disease field, acupuncture has been used for treating renal colic (28) and for extracorporeal shock wave lithotripsy (SWL) -related pain and anxiety (30,37,(39)(40)(41)(42).…”
Section: Historical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In one study, electroacupuncture was found to be an effective method for inducing sedation with analgesia without any demonstrable side effects. 16 Ulett reported that electroacupuncture to classic acupuncture points is associated with a deep calming effect. 17 In a prospective, randomised, placebo controlled, double blinded study, electroacupuncture was shown to reduce anxiety, discomfort, and demand for sedative drugs during colonoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, chronic knee pain has a more prominent sensory component and responds well to acupuncture but less well to the touch. There were positive trends in a number of small studies, indicating areas where further research would be useful: conditions include extracorporeal shock wave therapy, 11 post-operative pain, 12 insomnia in pregnancy, 13 and possibly hyperemesis gravidarum, 14 especially in view of the previous positive study. 15 In addition, there are new reports from 2005 that support previous research into the value of acupuncture in the rather surprising areas of pruritus due to uraemia, 16 and male infertility.…”
mentioning
confidence: 99%